Malignant Brain Tumors : State-of-the-Art Treatment - Moliterno Gunel, Jennifer; Piepmeier, Joseph M.; Baehring, Joachim M. (Springer International Publishing : Imprint: Springer, 2017)
This text addresses all aspects of patient evaluation and care. This includes new findings in imaging that provide a better understanding of the extent of the lesion as well as its relationship with critical neuroanatomic function. The evolution of intraoperative imaging, functional brain mapping,and technology to identify tumor from brain is covered. This has significantly improved the ability of surgeons to more safely and aggressively remove tumors.More importantly, a better understanding of tumor biology and genomics has created an opportunity to significantly revise tumor classification and better select optimal therapy for individual patients. The text covers novel and innovative treatment options including immunotherapy, tumor vaccines, antiangiogenic agents,and personalized cancer treatment. In addition, novel agent delivery techniques are covered to offer the potential for increasing the effectiveness of treatment by delivering active agents directly where they are needed most. Malignant Brain Tumors: State-of-the-Art Treatment provides a comprehensive overview of treatment for malignant gliomas, and will prove useful by updating physicians on new therapeutic paradigms and what is on the horizon for the near future. This text will be informative for surgeons, oncologists, neurologists, residents and students who treat these patients,as well as those who are training for a career in managing patients with these challenging tumors. .
Keywords: Medicine.; Neurosurgery.; Surgical oncology.; elektronické knihy; electronic books